The distributional dimension of the resource curse: Commodity price shocks and income inequality - Soran Mohtadi; David Castells-Quintana (Structural Change and Economic Dynamics, 2021)
How does high dependence on natural resources affect income inequality? Surprisingly little is known about the impact of dependence on primary goods on income distribution. Building on insights from the resource curse literature, this paper studies the relationship between income shocks through changes in commodity prices and income inequality in a panel of 80 countries from 1990 to 2016. We analyze differentiated effects of commodity price shocks depending on the type of commodity (labor vs. capital-intensive). We also study differences across world regions and explore potential mechanisms by looking at different types of inequality (pay-driven vs. capital-rents-driven). Results show that commodity price shocks have an impact on income inequality. However, this impact depends on the type of commodity and inequality.
Keywords: 330; resource curse; commodity price shocks; inequality; natural resources; resource booms; development